Identification of bacteria species isolated from soil and investigation of optimum conditions: application in food industry and biotechnological fields - Enez, Baris (Progress in Nutrition, 2019)
In this study, soil samples were taken. Isolation of bacteria was carried out by dilutions technique. Identification and biochemical tests of the obtained bacteria were performed. Bacteria were identified to be Bacillus cereus WYS01, Bacillus niacini PRPB1, Bacillus thuringiensis VITLW1, Bacillus thuringiensis ES2I3P, Bacillus cereus TG16. As a result of biochemical tests, all bacteria showed gram (+), urease tests (-) and amylase activity (+) results. Bacteria reproduced in different feed-lots showed most reproduction in Nutrient Agar and MRS Agar. By determining the optimum reproducing conditions of the bacteria, all bacteria were found to be the most reproductive at 40oC, pH 7.0 within 24 hours.